2012
DOI: 10.1161/circep.111.967265
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Ventricular Fibrillation in Right Ventricular Failure Secondary to Chronic Pulmonary Hypertension

Abstract: Background Right ventricular failure (RVF) in pulmonary hypertension (PH) is associated with increased incidence of sudden death by a poorly explored mechanism. Here we test the hypothesis that PH promotes spontaneous ventricular fibrillation (VF) during a critical post-PH onset period characterized by a sudden increase in mortality. Methods and Results Rats received either a single subcutaneous dose of monocrotaline (MCT, 60 mg/kg) to induce PH-associated RVF (PH, n=24) or saline (CTRL, n=17). Activation pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 39 publications
3
67
0
Order By: Relevance
“…predominantly in RVH rabbits (Panyasing et al, 2010). It has been demonstrated previously that electrical remodeling especially in the right ventricle is the proximate cause of arrhythmias (Benoist, Stones, Drinkhill, Bernus, & White, 2011;Tanaka, Takase, & Yao, 2013;Umar et al, 2012). In the current study, both prolongation of repolarization and increased transmural dispersion of repolarization were observed in rabbits with RVH suggesting the tendency to increase arrhythmogenic risk in PAB rabbits.…”
Section: Electrical Remodeling Of the Ventriclementioning
confidence: 94%
See 3 more Smart Citations
“…predominantly in RVH rabbits (Panyasing et al, 2010). It has been demonstrated previously that electrical remodeling especially in the right ventricle is the proximate cause of arrhythmias (Benoist, Stones, Drinkhill, Bernus, & White, 2011;Tanaka, Takase, & Yao, 2013;Umar et al, 2012). In the current study, both prolongation of repolarization and increased transmural dispersion of repolarization were observed in rabbits with RVH suggesting the tendency to increase arrhythmogenic risk in PAB rabbits.…”
Section: Electrical Remodeling Of the Ventriclementioning
confidence: 94%
“…Previous studies demonstrated that right ventricular failure following pulmonary hypertension and right ventricular hypertrophy is associated with increased incidence of cardiac sudden death; however, the underlying mechanism is unclear (Umar et al, 2012). Therefore, there is a need for an animal model of right ventricular hypertrophy.…”
Section: Importance Of the Model And Translational To Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…The LVs of these hearts did not develop fibrosis. 33 Yen et al 34 found that 3 weeks after MCT injection, the rats suffered from RV fibrosis, had high expression of fibrotic biomarkers (transforming growth factor β [TGFβ], p-SMAD3) in the RV, and low expression of antifibrotic biomarkers (bone morphogenetic protein 2 [BMP2], p-SMAD1/5). Treatment with a combination of sildenafil and bone marrow-derived EPCs was able to reverse these changes to levels almost equal to those of healthy rats, and this combination was more potent than either of the two therapies alone.…”
Section: Pah-induced Rvf and Interstitial Myocardial Fibrosismentioning
confidence: 99%